Co-ingestion of nutritional ergogenic aids and high-intensity exercise performance - Naderi, A.; Earnest, C. P.; Lowery, R. P.; Wilson, J. M.; Willems, M. E. T. (Sports Medicine, 2016)
Many sports involve repeated bouts of high-intensity exercise. High-intensity exercise is compromised, however, by the early onset of exercise-induced fatigue. Metabolic by-products, ion dysbalance and amount of phosphocreatine are considered the main peripheral causes of fatigue during high-intensity exercise. Intake of nutritional ergogenic aids is commonplace to enhance performance of high-intensity exercise by offsetting the potential mechanisms of fatigue. Creatine, probably one of the best known nutritional aids to enhance performance of high-intensity exercise, has convincingly substantiated its ergogenic potential. Although multi-ingredient supplements are now common, the justification for effectiveness is mostly based on observations with single intake of those ingredients. In this narrative review, the main focus is on the evidence of the effect of co-ingestion of ergogenic aids on performance of high intensity exercise for which the single intake has shown beneficial effects on high-intensity performance.